Tari Jaran Endut, dari Cerita Rakyat ke Tari Kontemporer - Putu Gita Rahayu Putriandini; I Gusti Ngurah Sudibya; Ida Ayu Wayan Arya Satyani (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
Jaran Endut Dance is a contemporary dance originating from the folklore of West Nusa Tenggara. Raising the history of the formation of Dusun Endut from the privilege of a horse. The idea of working on this work is the spirit of Jaran Endut in his long journey of helping the people of Pejarakan. The theme used is toughness. Toughness is manifested in the agility, dexterity, sharpness, and speed of the horse in moving. The creator felt challenged to bring an animal character; horse, into the human body. Visualizing the character of a horse requires agile body movements, expression and character deepening, so that the characteristics of the Jaran Endut dance can be conveyed. In addition,